Pembuatan Bioplastik berbahan Kulit Mangrove dan Tepung Tapioka serta Pengujian Daya Serap Airnya - La Mardani Putra; Yustisia Puspita; Anjeli Tri Ardia Reviana; M. Mahfudz Fauzi Syamsuri (Integrated Lab Journal, 2023)
Today, the problem of conventional plastics whose raw materials are derived from petroleum derivatives is still the center of attention because they are difficult to degrade. To overcome these problems, various efforts have been made, one of which is by utilizing bioplastics from natural fibers and starch. The purpose of this research is to fabricate mangrove bark fiber composites with tapioca starch into bioplastics and test their water absorption. Bioplastics were made by melt intercalation method with the addition of glycerol as plasticizer. The resulting bioplastics were characterized by FT-IR and tested for water absorption. The water absorption of bioplastics from fibers without NaOH-soaked was the highest at 5.54%. Bioplastics from and with NaOH immersion had the highest water absorption of 3.59%. Thus it can be said that bioplastics from NaOH-soaked fibers are better than bioplastics from fibers without NaOH-soaked.